The importance of multiprofessional treatment of a patient with arthrogryposis: Case report (Research, Society and Development, 2022)
Arthrogryposis multiplex congenita (AMC) is a rare syndrome, defined by a set of non-progressive congenital malformations, accompanied by multiple rigid contractures. The etiology is not defined, its diagnosis is complex and 75% of the time it is performed late. Monitoring with the multidisciplinary team is essential, aiming at the well-being and quality of life of the patient. Physiotherapy should be started early, with the main objectives being functional acquisition, autonomy in performing activities of daily living, prevention of deformities and independent gait. The objective of this study is to report the case of a patient with AMC, as well as the importance of multiprofessional follow-up in the treatment, prevention, improvement and maintenance of quality of life. This is a case report, carried out in a Specialized Center for Craniofacial Anomalies, located in western Paraná, based on anamnesis, clinical and physical examination, interview with the person in charge and weekly appointments. A 13-year-old male patient has distal arthrogryposis multiplex congenita, which was diagnosed at 16 days of life. He started follow-up with physiotherapy since 45 days, and is currently being followed up with the multidisciplinary team of that center. The response of the proposed multiprofessional treatment plan was very positive, allowing the patient to overcome their difficulties, make adaptations to their activities of daily living, and have a better quality of life. It is important to emphasize the need for follow-up with a specialized multidisciplinary team, given the complexity of AMC.